Idāratu Takhṭīṭ Barnāmij Al-Masraḥīyyah Fī Manẓūr Mahārāt Al-Qarni Al-Ḥādī Wa Al-ʿIsyrīn - Firman Nurul Fauzi; Zakiyah Arifa (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2023)
Managing the planning in the program, in turn, serves as a guide for defining the strategy you will implement. On the other hand, twenty-first (21st) century skills are one of the skills that can help program planning. This study aims to describe the planning Masrahiyah program in the Arabic language education department. The descriptive qualitative method is applied due to the research aims, with interviews, observation, and documentation as the data collection method. Data analysis used the Miles and Huberman method of following instructions and data, presenting the data, and summarizing or deducing. The results of this research are: 1) Masrahiyan program has two models, top-down and bottom-up, and SWOT analysis is used to set goals in this program. 2) From the twenty-first (21st) century skill perspective, the Masrahiyah showed that it has many skills; communication, creativity, and cooperation. There needed to be more using language for some students because of a lack of interest in using the Arabic language.إدارة تخطيط سبب رئيسي في نجاح البرنامج بدورها كإرشاد لتعيين الإستراتجية التي ستطبقها في إجراء البرنامج. ومهارات القرن الحادي والعشرين هي إحدى المهارات التي يمكن مساعدتها في إدارة تخطيط البرنامج. تهدف هذا البحث لوصف عملية إدارة تخطيط برنامج المسرحية في قسم تعليم اللغة العربية بجامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج في منظور مهارات القرن الحادي والعشرين. المدخل الكيفي ونوع الوصفي هما منهجية البحث المستخدمة لوصف حالة واقعية شمولية وطبيعية على عملية إدارة تخطيط. وأما أسلوب جمع البيانات المستخدمة هي الملاحظة والمقابلة والوثائق. وتحليل البيانات المستخدمة هي طريقة ميلس و هوبرمان بثلاثة إجراءات يعني تحفيض البيانات وعرض البيانات والتلخيص أو الاستنتاج. ونتائج هذا البحث هي: 1) استخدام برنامج المسرحية نموذجين هي من الأعلى إلى الأسفل (top dwon) ومن الأسفل إلى الأعلى (bottom up) وتحليل SWOT الذي استخدامه لتعيين الأهداف في هذا المرنمج وأي الذي يتم الانتباه فيه. 2) وفي منظور مهارات القرن الحادي والعشرين أكثر المهارات المتدربة في إدارة تخطيط المسرحية هي المهارة التوصلية والابداعية والتعاونية. ولكن لم يوجد فيها كثيرا من عملية ترقية مهارات اللغوية، لأن فيها قلة الاهتمام في استخدام اللغة العربية إما مهارة اللغة الستقبالية أو الإنتاجية.